Effect of combination of all-trans retinoic acid and arsenic trioxide on apoptosis of acute promyelocytic leukemia cells - Hu, Jiane; Sun, Qiuyan; Fang, Wei; Wang, Qinglin (Cellular and Molecular Biology, 2019)
To study the effect of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) combination treatment on apoptosis of acute promyelocytic leukemia cells (NB4), inflammation and prognosis. The effect of ATRA - ATO combination on the proliferation of NB4 was determined using MTT assay. Apoptosis of NB4 cells was assessed with TUNEL assay. The effect of ATRA-As2O3 combination on the expressions of IL-6 and TNF-Î± in NB4 cells was determined using ELISA kits, while its effect on the quality of life of 25 acute promyelocytic leukemia patients admitted to our hospital was scored, as an index of prognosis. The combination treatment with ATRA and ATO significantly inhibited the proliferation of NB4 cells and promoted their apoptosis, relative to the model group. In addition, the combination treatment reduced serum IL-6 and TNF-Î± levels in patients with acute promyelocytic leukemia, and improve their quality of life and survival. Combination treatment with ATRA and ATO significantly inhibits the proliferation of NB4 cells and promotes their apoptosis, and reduces inflammatory responses in patients with acute promyelocytic leukemia, while improving their quality of life and prognosis.